ESTIMASI KETIDAKPASTIAN PENGUKURAN DALAM PENGUJIAN KUAT TEKAN BETON - N. Retno Setiati (Jurnal Jalan-Jembatan, 2006)
Compliance testing sometimes involves measured values, which lie close to the zone of uncertainty. A different method of uncertainty evaluation by foreign authority could mean rejection of a container of goods destined for import because of expansion of the recalculated zone of uncertainty. In the era of global marketplace it is imperative that the method for evaluating and expressing uncertainty be uniform throughout the world so that measurements performed in different countries can be easily compared. This study gives the recommended method for evaluating me asurement uncertainty that is applicable for calibration and testing laboratories which based on SNI-19-17025-2000. The method of evaluating measurement uncertainty described in this studies in accordance with ISO â€œGuide to the Expression of Uncertainty in Measurementâ€.